PEMANFAATAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM PENGKLASIFIKASIAN BAHAYA EROSI PADA DAS TALAWAAN - PRAYITNO PRAYITNO; Johny S. Tasirin; Maria Y.M.A. Sumakud; Johana A. Rombang (Universitas Sam Ratulangi, 2015)
ABSTRACT Talawaan watershed is one of the most important watershed in North Minahasa Regency. Erossion in the Talawaan watershed results in decreasing land resource quality caused by both natural and human activities. This research aims to study the erosion hazard level in Talawaan watershed. Method to calculate erosion rate is based on USLE equation (Wischmeir and Smith, 1978) utilizing Geographic Information Systems (GIS). Result shows that the erossion hazard levels in Talawaan Watershed were â€œvery lightâ€ 2.791,56 ha (21,49%), â€œlightâ€ 4.019,46 ha (30,94%), â€œmediumâ€ 3.127,86 ha (24,08%), â€œheavyâ€ 2.521,79 ha (19,41%), and â€œvery heavyâ€ 528,88 ha (4,07%). Talawaan watershed has an average erosion rate of 60.53 tonnes/ha/year which is â€œmediumâ€ erosion hazard level. The results of this study may be used to a better management plan of Talawaan watershed. Keywords: TBE, GIS, USLE, DAS Talawaan.Â